Investing in a better food future: the innovative role of food partnerships | Sustain
As the cost of living crisis continues to affect communities and supply chain disruptions further put pressure on food access, now is the time to invest in local food economies and community food access – into production, distribution and infrastructure that improve access to healthy and sustainable food, creating good food jobs, fair returns for farmers, healthy communities and a pride of place. This briefing makes the case for harnessing the power and vision of Sustainable Food Places food partnerships to deliver the above, and for a Good Food Bill in every UK nation to set a long-term and consistent strategy on food.